Régime foncier pastoral en Éthiopie - Johan Helland (VertigO)
The proposed paper will examine contemporary land and resource tenure arrangements in the pastoral areas of Ethiopia. National land tenure legislation, arising from conditions within arable agriculture in the highlands, is now made increasingly relevant also in the lowlands. Indigenous tenure arrangements therefore articulate with the national legislation to create a new tenure situation. The restructuring of tenure arrangements in pastoral societies may be seen as an aspect of the general process of marginalisation of pastoral society in Ethiopia. The outcome of these processes of marginalisation will have grave implications for the communal resource management regimes that have sustained Ethiopian pastoralism. Changes in national tenure arrangements also distribute local user rights in new ways. A disturbing trend is the on-going exclusion of pastoralists from critically important key resources. Resource poverty is thus becoming a major aspect of poverty in pastoral society.